Sustainable aviation fuels: a review of production technologies, life-cycle emissions, and key challenges - Aaqib Zafar; Muhammad Nauman; Muhammad Usman; Rashid Ali Laghari; Muhammad Imran Akhtar; Azhar Abbas Khosa; Muhammad Kashif Shahzad; Abdur Rahman Shaukat; Sheikh Muhammad Farhan; Muhammad Hamid Abbas; Longfei Chen (Fuel, 2027)

Use of wild edible plants: A comparative analysis of seven plant species for potential food applications - Ehsan Ali; Muhammad Farooq Azhar (Food and Humanity, 2026)

Draft nuclear and complete mitochondrial genome assemblies of the flare-horned markhor (Capra falconeri): genomic resources for conservation and phylogenetics - Javeria Wali; Muhammad Waqas; Azhar Hussain Shah; Inam Ullah; Asif Mir; Zunnan Huang; Amjad Ali (Mammalian Genome, 2026)

Mode of inheritance of spinosad resistance in the rice weevil, Sitophilus oryzae (Coleoptera: Curculionidae) - Hafiz Azhar Ali Khan (Journal of Stored Products Research, 2026)

Improving tooth enamel remineralization with laser-assisted colloidal platinum nanoparticles: a new alternative to fluoride-based treatments - Fattin A. Fadhil; Azhar M. Haleem; Ahlam Taha Mohammed; Abdulrahman Khalaf Ali (Toxicology and Environmental Health Sciences, 2026)

Age-stage, two-sex life table analysis reveals transgenerational lethal and sublethal impacts of Beauveria bassiana on Spodoptera frugiperda - Tiyyabah Khan; Hafiz Azhar Ali Khan (Crop Protection, 2026)

Microwave-induced eustress in Datura innoxia: Integrated photosynthetic, oxidative, and cellular responses to a low-dose hormetic elicitor - M. Masroor A. Khan; Tahoora Batool; Azhar Ali; Saif Ali Khan; M. Naeem; Mohammad Mukarram (Biocatalysis and Agricultural Biotechnology, 2026)

Feature Selection and Data Decomposition-Driven Drought Forecasting: Designing Hybrid Deep Learning Models - Ayesha Parveen; Muhammad Azhar; Muhammad Gulistan; Mumtaz Ali; Aitazaz A. Farooque (Water Resources Management, 2026)

Hybrid deep learning approach for detecting and classifying space debris in low Earth orbit - Eman Mahmoud; Syed Saad Azhar Ali; Abdul Jabbar Siddiqui (Journal of Space Safety Engineering, 2026)

Tailoring strontium-nickel supported reduced graphene oxide nanostructure for synergistic catalytic hydrogen generation from sodium borohydride and photodegradation of organic pollutant - Rana Nauman Hassan; Faryal Ali; Shoaib Akhtar; Abu Bakar Siddique; Khaled Fahmy Fawy; Muhammad Sher; Muhammad Ashraf Shaheen; Muhammad Fayyaz ur Rehman; Umar Nishan; Tauqeer Ahmad; Arshad Ali; Azhar Abbas (Fuel, 2026)

Genetic Diversity and Population Structure of 72 Turkish Ficus carica (L.) Genotypes Assessed Using SCoT Markers - Meliha Feryal Sarıkaya; Muhammad Azhar Nadeem; Sarmad Ali Qureshi; Mehmet Bedir; Muhammed Tatar; Amjad Ali; Muhammad Tanveer Altaf; Viyan Acar Uçer; Kağan Kökten; Erdal Aglar; Faheem Shehzad Baloch (Biochemical Genetics, 2026)

Epidemiological study of Crimean- Congo haemorrhagic fever in Thi Qar (2023–2024): assessing the role of tick bites, household animals, slaughter and fresh meat exposure in disease transmission - Saja Abdalkadhum Hommod; Azhar kareem Razzaq; Ali B. Roomi (VirusDisease, 2026)

Tagetes minuta L. Extract Ameliorates Epilepsy: Modulating Neuroinflammatory Pathways via Altering Brain-Derived Neurotropic Factor and Interleukin-6 Levels - Maryum Mumshad Raja; Humaira Naureen; Fawad Ali Shah; Sadia Adil; Arooj Mohsin Alvi; Rabia Khan; Sundas Safdar; Farah Azhar; Shahana Khattak (Journal of Pharmaceutical Innovation, 2026)

Evaluation of Alternaria alternata and A. tenuissima as novel entomopathogenic agents against Trogoderma granarium, Tribolium castaneum, and Rhyzopertha dominica - Tiyyabah Khan; Hafiz Azhar Ali Khan; Naeem Iqbal (Journal of Stored Products Research, 2026)

Charcoal rot in sesame: infection biology, host resistance mechanism, and genomic-enabled strategies for durable resistance breeding - Amjad Ali; Muhammad Azhar Nadeem; Fatih Ölmez; Cemal Kurt; Faheem Shehzad Baloch (Theoretical and Applied Genetics, 2026)
Sesame ( Sesamum indicum L.) is a globally important oilseed crop, but its production is constrained by charcoal rot, caused by the soil-borne fungus Macrophomina phaseolina. The pathogen’s exceptionally broad host range, long-term soil persistence through microsclerotia, and increased aggressiveness under high temperature and drought make charcoal rot a major destructive constraint in sesame-growing regions. This review integrates current knowledge on the biology, epidemiology, infection processes, and genetic population variability of Macrophomina spp. in relation to charcoal rot development in sesame. We also summarize key host resistance mechanism including pathogen perception, cell wall reinforcement, phenylpropanoid-mediated defense, antioxidant responses, and associated physiological and molecular adaptations. Particular attention is given to the challenges of resistance screening under variable environmental conditions, including heat- and drought-associated disease expression and pathogen diversity, which complicate the identification of stable resistance sources. The review further examines progress in sesame improvement through germplasm characterization, mutation breeding, interspecific introgression, high-throughput phenotyping, and genomic-assisted approaches such as QTL mapping, genome-wide association studies (GWAS), marker-assisted selection, genomic selection, and functional validation. Integrating these tools with multi-omics and gene-editing strategies offers a promising route for accelerating the development of durable, climate-resilient charcoal rot resistance cultivars. Broader use of diverse germplasm, standardized multi-environment phenotyping, and international collaboration will be essential for sustainable resistance breeding and future sesame production.

Assessment of urban and peri-urban grazing practices from herders and local community perspective in the semiarid region of Pakistan - Muhammad Farooq Azhar; Ghulam Yasin; Asghar Ali; Abida Aziz; Ghulam Yasin; Daniyal Hussain; Ehsan Ali (Environmental Monitoring and Assessment, 2026)

Exploring the Role of Mitochondrial Sirtuin 3 Gene in Gastric Cancer Risk Based on SNP Analysis and LORD-Q Assay - Ishrat Mahjabeen; Muhammad Zahid Hussain; Maria Fazal-Ul Haq; Azhar Mehmood; Muhammad Shahbaz Haris; Shereen Ali Khan; Anum Chaudhry; Farzana Hakim; Ayesha Zulfiqar Abbasi; Mahmood Akhtar Kayani (Biochemical Genetics, 2026)

Integrated Mechanical–NDT Evaluation of Moisture- and Weathering-Induced Weakening in Granite, Marble, and Limestone Joints - Waqas Ahmed; Azhar Ali; Abdul Rahim Asif; M. E. Al-Atroush; Muhammad Yasir (Rock Mechanics and Rock Engineering, 2026)

Multigenerational exposure to the fungicide tebuconazole reveals hormetic effects on the demography and biology of a non-target vector mosquito Aedes albopictus - Hafiz Azhar Ali Khan; Tiyyabah Khan (Aquatic Toxicology, 2026)

Sublethal effects of azadirachtin on life table parameters of Musca domestica (Diptera: Muscidae): implications for population dynamics in Pakistan - Naeem Iqbal; Nauman Sadiq; Hafiz Azhar Ali Khan; Allah Ditta Abid; Muhammad Sohail Shahzad; Muhammad Nadir Naqqash; Adnan Akhter (International Journal of Tropical Insect Science, 2026)

Toxicity and sublethal effects of fluralaner on the development of Spodoptera frugiperda (Lepidoptera: Noctuidae) - Hafiz Azhar Ali Khan; Tiyyabah Khan (Crop Protection, 2026)

Enhanced charge carrier separation in greenly synthesized ZnO-NiO NCs-based Z-scheme heterojunction for photodegradation of ciprofloxacin hydrochloride and hydrogen evolution reaction - Abu Bakar Siddique; Muhammad Ashraf Shaheen; Azhar Abbas; Shoaib Akhtar; Muhammad Shahzad; Akbar Ali; Nadeem Ahmad; Hatem A. Abuelizz; Rashad Al-Salahi (Fuel, 2026)

Corrigendum to “Simultaneous removal of Mn²⁺ and Sr²⁺ from wastewater via microbially induced carbonate precipitation (MICP) using immobilized Bacillus licheniformis K-1: A sustainable bioremediation approach” [J Hazard Mater 501 (2026) 14065] - Kashif Ali Memon; Huaxiao Yan; Muhammad Mujahid; Jiabin Geng; Shuqi Wang; Runxi Yin; Yueming Zhao; Akash Kumar; Azhar Ali Laghari; Zuozhen Han; Na Guo; Hui Zhao (Journal of Hazardous Materials, 2026)

Simultaneous removal of Mn²⁺ and Sr²⁺ from wastewater via microbially induced carbonate precipitation (MICP) using immobilized Bacillus licheniformis K-1: A sustainable bioremediation approach - Memon Kashif Ali; Huaxiao Yan; Muhammad Mujahid; Jiabin Geng; Shuqi Wang; Runxi Yin; Yueming Zhao; Akash Kumar; Azhar Ali Laghari; Zuozhen Han; Na Guo; Hui Zhao (Journal of Hazardous Materials, 2026)

Unveiling genetic diversity and population structure in lentil (Lens culinaris) germplasm through scot markers - Sarmad Ali Qureshi; Muhammad Azhar Nadeem; Meliha Feryal Sarıkaya; Amjad Ali; Muhammed Tatar; Muhammad Tanveer Altafl; Dilek Tekdal; Muhammad Kashif Ilyas; Seyithan Seydoşoğşu; Sezai Ercişli; Kağan Kökten; Faheem Shahzad Baloch (Molecular Biology Reports, 2025)

Projecting future climate extremes in the glacier-fed upper indus basin using machine learning based downscaling of CMIP6 GCMs - Muhammad Amjad Saleem; Muhammad Shoaib; Sarfraz Hashim; Muhammad Shoaib; Hafiz Umar Farid; Muhammad Ismail; Mubashir Ali Ghaffar; Ahmad Mujtaba; Jinwook Lee; Muhammad Azhar Inam; Arshad Ameen (Theoretical and Applied Climatology, 2025)

Risk assessment of synthetic insecticides and botanicals to Western honey bee, Apis mellifera (Hymenoptera: Apidae) - Sami Ullah; Naeem Iqbal; Muhammad Sohail Shahzad; Hafiz Azhar Ali Khan; Khalid Rafiq; Allah Ditta Abid; Mudssar Ali; Shafqat Saeed (International Journal of Tropical Insect Science, 2025)

Machine learning-based streamflow projections in the upper indus basin under CMIP6 climate scenarios - Muhammad Amjad Saleem; Muhammad Shoaib; Sarfraz Hashim; Muhammad Shoaib; Hafiz Umar Farid; Mubashir Ali Ghaffar; Muhammad Ismail; Arshad Ameen; Jinwook Lee; Muhammad Azhar Inam; Changhyun Jun (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Ferroptosis: a novel pathway in the pathogenesis and treatment of endometriosis - Xunshu Cheng; Muhammad Azhar Memon; Waseem Ali; Yonggang Ma (Journal of Molecular Histology, 2025)

Molecular screening of stripe rust and powdery mildew resistance genes in European bread wheat using the validated gene-specific SSR markers - Rada Šućur; Amjad Ali; Parnaz Mortazavi; Velimir Mladenov; Bojan Jocković; Jin Ying Gou; Muhammad Azhar Nadeem; Faheem Shehzad Baloch; Yong Suk Chung (Physiological and Molecular Plant Pathology, 2025)

Biocontrol potential of isolates of Aspergillus flavus and Aspergillus parasiticus against Rhyzopertha dominica, Trogoderma granarium, and Tribolium castaneum - Hafiz Azhar Ali Khan; Tiyyabah Khan; Naeem Iqbal (Journal of Stored Products Research, 2025)

Influence of temperature and relative humidity on the combined efficacy of insecticides and diatomaceous earth for the control of Trogoderma granarium on rough rice - Muhammad Bukhari; Hafiz Azhar Ali Khan (Journal of Stored Products Research, 2025)

A comprehensive review on the recovery of lithium from lithium-ion batteries and spodumene - Asad Ali; Sadia Afrin; Abdul Hannan Asif; Yasir Arafat; Muhammad Rizwan Azhar (Journal of Environmental Management, 2025)

A comparative analysis of diamond nanoparticles prepared by pulsed laser for antibacterial application against Streptococcus mutans - Fattin A. Fadhil; Ahlam Taha Mohammed; Azhar M. Haleem; Abdulrahman Khalaf Ali (Toxicology and Environmental Health Sciences, 2025)

N-AquaRAM: A Cost-Efficient Deep Learning Accelerator for Real-Time Aquaponic Monitoring - Ali Siddique; Muhammad Azhar Iqbal; Jingqi Sun; Xu Zhang; Mang I. Vai; Sunbal Siddique (Agricultural Research, 2025)
Aquaponics is an emerging area of agricultural sciences that combines aquaculture and hydroponics in a symbiotic way to increase crop production. Though it offers a lot of advantages over traditional techniques, including chemical-free and soil-less farming, its commercial application suffers from some problems such as the lack of experienced manpower. To operate a stable smart aquaponic system, it is critical to estimate the fish size properly. In this context, the use of dedicated hardware for real-time aquaponic monitoring can greatly resolve the issue of inexperienced handlers. In this article, we present a complete methodology to train a deep neural network to perform fish size estimation in real time. To achieve high accuracy, a novel implementation of swish function is presented. This novel version is far more hardware efficient than the original one, while being extremely accurate. Moreover, we present a deep learning accelerator that can classify 40 million fish samples in a second. The dedicated real-time system is about 1600 times faster than the one based on general-purpose computers. The proposed neuromorphic accelerator consumes about 2600 slice registers on a low-end model of Virtex 6 FPGA series.

Negative influence of suboptimal quality of drinking water on avian coronavirus pathogenesis and immune response: A Controlled Study - Muhammad Farooq; Awais Ghaffar; Ahmed Ali; Ryan Rahimi; Muhammad Azhar; Ishara M. Isham; Heshanthi Herath-Mudiyanselage; Sufna M. Suhail; Mohamed Faizal Abdul-Careem (Veterinary Immunology and Immunopathology, 2025)

Linking government support, and quality management with sustainable energy project success: mediating role of community participation and moderating role of project governance - Shahid Hussain; Tasawar Baig; Saadia Beg; Azhar Ali (Innovative Infrastructure Solutions, 2025)

Exploring genetic diversity of Turkish fig (Ficus carica L.) germplasm using inter-Primer Binding Site (iPBS) retrotransposon markers - Viyan Acar Uçer; Erdal Aglar; Parnaz Mortazavi; Sarmad Ali Qureshi; Amjad Ali; Muhammed Tatar; Muhammad Tanveer Altaf; Mehmet Bedir; Sezai Ercişli; Muhammad Azhar Nadeem; Faheem Shehzad Baloch (Genetic Resources and Crop Evolution, 2025)

Effectiveness of pirimiphos-methyl, alpha-cypermethrin, spinetoram and thiamethoxam alone and in combination with diatomaceous earth for the control of Trogoderma granarium on rough rice - Muhammad Bukhari; Hafiz Azhar Ali Khan (Journal of Stored Products Research, 2025)

A parametric study of particle size influence on sewage sludge-derived hydrochar and coal char co-gasification: Reactivity and carbon conversion analysis - Azhar Ali Laghari; Asma Leghari; Akash Kumar; Lata Kumari; Muhammad Rizwan; Qurat-ul-ain Abro; Memon Kashif Ali; Yongheng Shen; Qingxia Guo (Biomass and Bioenergy, 2025)

Impacts of climate change on Pakistan’s weather patterns: a comprehensive study of temperature and precipitation trends - Hafiza Nida; Muhammad Kashif; Azhar Ali Janjua; Muhammad Aslam; Kamil Shahzad Cheema; Sami Ullah (Environmental Monitoring and Assessment, 2025)

Sublethal and hormetic effects of the fungicide tebuconazol on the biology of a nontarget pest insect, Musca domestica - Hafiz Azhar Ali Khan; Tiyyabah Khan; Naeem Iqbal (Science of The Total Environment, 2025)

ENSO teleconnections and predictability of the boreal summer temperature over the Arabian Peninsula in C3S and Saudi-KAU seasonal forecast systems - Mansour Almazroui; M. Salman Khalid; Muhammad Adnan Abid; Irfan Ur Rashid; Shahzad Kamil; Haroon Siddiqui; M. Nazrul Islam; Muhammad Ismail; Muhammad Azhar Ehsan; Enda O'Brien; Mazen Asiri; Rayees Ahmed; et al. (Atmospheric Research, 2025)

Nano-revolution in aquaculture: quantum dot innovations for sustainable fisheries - Ulfat Batool; Syed Makhdoom Hussain; Shafaqat Ali; Azhar Rasul; Muhammad Mudassar Shahzad; Adan Naeem; Nisar Ahmad; Muhammad Munir; Abdul Ghafoor; Mohammad Ali Alshehri (Aquaculture International, 2025)

Molecular screening of diverse Tomato germplasm for root-knot nematode resistance using the Mi23 marker - Parnaz Mortazavi; Amjad Ali; Muhammed Tatar; Fatih Ölmez; Muhammad Tanveer Altaf; Muhammad Azhar Nadeem; Hayriye Yildiz Dasgan; Boran Ikiz; Tuğçe Temtek; Ömer Faruk Bilgin; Ayşe Mücahitoğlu; Mahmut Bayram; et al. (Physiological and Molecular Plant Pathology, 2025)

Human health risks of heavy metals in water and vegetables: a deterministic and probabilistic study in Gilgit-Baltistan, Pakistan - Nafeesa Khatoon; Sartaj Ali; Azhar Hussain; Jia Huang; Zeyang Li; Zengli Yu; Hongyan Liu (Environmental Geochemistry and Health, 2025)

Food security in Punjab, Pakistan: rural views on climate disasters and their impacts - Muhammad Usman; Asghar Ali; Sajjad Ahmad Baig; Magdalena Radulescu; Azhar Abbas; Rimsha Akram (Environment, Development and Sustainability, 2025)

Acute toxicity of chloroxylenol detergent on the biology of Musca domestica - Jamila Fatima; Hafiz Azhar Ali Khan; Naeem Iqbal (International Journal of Tropical Insect Science, 2025)

Optimizing crowdfunding for mineral resources of Dutch economy: The role of fintech in achieving sustainable development goals through artificial intelligence - Usman Ahmad; Ameenullah Aman; Azam Anwer Khan; Syed Emad Azhar Ali (Resources Policy, 2025)

Applicability of Start Codon Targeted (SCoT) markers for the assessment of genetic diversity in bread wheat germplasm - Muhammad Tanveer Altaf; Muhammad Azhar Nadeem; Amjad Ali; Waqas Liaqat; Mehmet Bedir; Nurettin Baran; Aleksandra Ilić; Muhammad Kashif Ilyas; Abdul Ghafoor; Hamide Dogan; Muhammad Aasim; Faheem Shehzad Baloch (Genetic Resources and Crop Evolution, 2025)
Research endeavors focused on examining genetic diversity play a pivotal role in advancing agricultural practices, as they furnish valuable insights for breeding programs and the preservation of germplasm. Wheat holds significant global importance as a cereal crop, serving as a primary source of sustenance for almost one-third of the global human population. In the current study, a total of 80 bread wheat genotypes were characterized using the start codon targeted (SCoT) marker system. A set of 14 polymorphic primers yielded a cumulative count of 399 bands with an average of 28.05 bands per primer. The range of diversity markers, such as polymorphism information content (0.26–0.59), effective numbers of alleles (1.27–1.59), Shannon’s information index (0.30–0.51), and gene diversity (0.18–0.34), provided evidence of elevated genetic differences within the examined germplasm. According to the findings of the molecular variance analysis, greater genetic variations are found within populations (92%). The model-based structural approach partitioned the 80 bread wheat genotypes into two distinct populations (Population A and B). The diversity indices based on the structures of the populations revealed that population A had greater diversity compared to population B. Both the principal coordinate analysis and the neighbor-joining analysis also differentiated the 80 different bread wheat genotypes based on their respective collection points. The present crop diversity offers great opportunities for enhancing crop quality and increasing tolerance to environmental challenges, both of which will lead to a reduction in the problem of food insecurity.

Investigation of a broad diversity of nanoparticles, including their processes, as well as toxicity testing in diverse organs and systems - Azhar U. Khan; Mohammad Qutob; Amel Gacem; Mohd. Rafatullah; Krishna Kumar Yadav; Pankaj Kumar; Javed Khan Bhutto; Meenal Rehman; Sudhakar Bansoid; Lienda Bashier Eltayeb; Nazia Malik; Mohammed Azam Ali; et al. (Toxicology, 2024)

Chemical modification of Pinus walliichiana sawdust: Application in membrane system for efficient purification of groundwater containing Cd(II) and Ni(II) - Muhammad Imran Irfan; Mahnoor Sadiq; Lubna Zohra; Abu Bakar Siddique; Muhammad Yousaf; Madiha Rubab; Kishwar Urooj; Ambreen Aziz; Hira Ali; Mehreen Fatima; Hatem M.A. Amin; Hassan A. Alhazmi; et al. (Journal of Water Process Engineering, 2024)

Characterizing mode of inheritance of permethrin resistance in field strains of rice weevil Sitophilus oryzae (Linnaeus) from Pakistan - Hafiz Azhar Ali Khan; Tiyyabah Khan; Naeem Iqbal (Journal of Stored Products Research, 2024)

Applicability of SCoT markers in unraveling genetic variation and population structure among sugar beet (Beta vulgaris L.) germplasm - Nazlı Aybar Yalinkiliç; Sema Başbağ; Muhammad Tanveer Altaf; Amjad Ali; Muhammad Azhar Nadeem; Faheem Shehzad Baloch (Molecular Biology Reports, 2024)

Effects of dietary Arthrospira platensis phycocyanin on growth, fatty acid assessment of breast muscles, hematobiochemical, immunological responses, and hepatic histomorphology in broiler chickens - Shimaa A. Amer; Amany Behairy; Amr A. Moustafa; Azhar Eltanahy; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Ali Osman; Ahmed Gouda; Simon J. Davies; Samar A. Tolba (Journal of Applied Phycology, 2024)

Predicting permeability in sandstone reservoirs from mercury injection capillary pressure data using advanced machine learning algorithms - Faiq Azhar Abbasi; Areesha Sajjad; Mohsin Ayubi; Ghulam Haider; Shaine Mohammadali Lalji; Syed Imran Ali; Muneeb Burney (Arabian Journal of Geosciences, 2024)

Exploring the integrated potential of pyrolysis and low-temperature wet torrefaction for typical medical waste valorization: A multifaceted approach leveraging online TG-FTIR-MS, 2D-COS, iso-conversional kinetics, and reaction mechanisms - Akash Kumar; Lata Kumari; Azhar Ali Laghari; Hongwei Rong; Imtiaz Ali Jamro; Shahdev Sajnani; Moses Akintayo Aborisade; Gulzeb Rajput; Belay Tafa Oba; François Nkinahamira; Pamphile Ndagijimana; Ghazanfar Mehboob; et al. (Chemical Engineering Journal, 2024)

In silico genome-wide analysis of the growth-regulating factor gene family and their expression profiling in Vitis vinifera under biotic stress - Nimra Nazir; Azhar Iqbal; Hadia Hussain; Faisal Ali; Khalid S. Almaary; Most. Nazmin Aktar; Muhammad Sajid; Mohammed Bourhia; Ahmad Mohammad Salamatullah (Cell Biochemistry and Biophysics, 2024)

Toxicity of different nitrogenous fertilizers on Aedes aegypti larvae (Linnaeus) (Diptera: Culicidae) - Sikander Ali; Unsar Naeem-Ullah; Naeem Iqbal; Hafiz Azhar Ali Khan; Allah Ditta Abid; Muhammad Sohail Shahzad; Shafqat Saeed; Muhammad Usman; Muhammad Nadir Naqqash (International Journal of Tropical Insect Science, 2024)

Greenly synthesized zinc oxide nanoparticles: An efficient, cost-effective catalyst for dehydrogenation of formic acid and with improved antioxidant and phyto-toxic properties - Sami Ullah; Muhammad Shaban; Abu Bakar Siddique; Anam Zulfiqar; Naveed Shahzad Lali; Muhammad Naeem-ul-Hassan; Muhammad Imran Irfan; Muhammad Sher; Muhammad Fayyaz ur Rehman; Ali Hanbashi; Fahad Y. Sabei; Hatem M.A. Amin; et al. (Journal of Environmental Chemical Engineering, 2024)

Editing microbes to mitigate enteric methane emissions in livestock - Faheem Ahmed Khan; Azhar Ali; Di Wu; Chunjie Huang; Hamza Zulfiqar; Muhammad Ali; Bilal Ahmed; Muhammad Rizwan Yousaf; Ezi Masdia Putri; Windu Negara; Muhammad Imran; Nuruliarizki Shinta Pandupuspitasari (World Journal of Microbiology and Biotechnology, 2024)

Investigation of genetic diversity among autochthonous grape cultivars grown in Türkiye using molecular primers - Ahmet Sümbül; Ercan Yildiz; Ali Sabir; Muhammad Azhar Nadeem (Genetic Resources and Crop Evolution, 2024)
Grape is a type of fruit widely grown globally and in Türkiye thanks to its importance in human nutrition and diversity of usage areas. Türkiye has a long history of grape cultivation, and the genetic diversity of local grapes grown in some regions has still not been revealed. This study showed the genetic diversity between 60 local grape genotypes selected from north Central Anatolia and nine reference grape cultivars;10 inter simple sequence repeats (ISSR) and 7 inter-primer binding site (IPBS) retrotransposon primers were used. The mean values of genetic diversity indices in ISSR and IPBS retrotransposon primers were calculated as expected allelic frequency (p) 0.476/0.195, observed allelic frequency (q) 0.524/0.805, number of effective alleles (Ne) 1.326/1.378, Shannon’s information index (I) 0.308/0.367, expected heterozygosity (He) 0.199/0.232 and unbiased expected heterozygosity (uHe) 0.201/0.234, respectively. Unweighted pair group method with arithmetic mean (UPGMA) and model-based STRUCTURE analysis divided the studied germplasm into two groups. However, local genotypes were not grouped per the regions where they grew. As a result of the analysis of molecular variance (AMOVA) analysis, the inter-population variation was determined to be 11%, and the intra-population variation was determined to be 89%. The mean genetic differentiation value (Fst) between populations was 0.303. The results showed that ISSR and IPBS retrotransposon primers effectively explained the genetic diversity.

Integrative approach to mitigate chromium toxicity in soil and enhance antioxidant activities in rice (Oryza sativa L.) using magnesium–iron nanocomposite and Staphylococcus aureus strains - Muhammad Azhar Ali; Muhammad Fahad Sardar; Afzal Ahmed Dar; Mohsin Niaz; Jawad Ali; Qian Wang; Yu Zheng; Yadan Luo; Gadah Albasher; Fengmin Li (Environmental Geochemistry and Health, 2024)

Methanolic extracts of litchi (Litchi chinensis Sonn.): A novel approach of targeting glucose-6-phosphate dehydrogenase for liver cancer therapy - Lubna Kanwal; Shaukat Ali; Azhar Rasul; Sana Shahbaz; Habiba Anum; Tooba Nauroze (Toxicon, 2024)

Control efficacy of isolates of Aspergillus nidulans and Aspergillus fumigatus against three destructive insect pests of stored grain - Hafiz Azhar Ali Khan; Tiyyabah Khan; Naeem Iqbal; Waheed Anwar; Muhammad Ali (Journal of Stored Products Research, 2024)

Frontiers in bacterial-based green synthesized nanoparticles (NPs): A sustainable strategy for combating infectious plant pathogens - Amjad Ali; Muhammad Aasim; Kübra Çelik; Muhammad Azhar Nadeem; Faheem Shehzad Baloch (Biocatalysis and Agricultural Biotechnology, 2024)

Molecular Phylogenetics of Green-Eyed Skimmers Macromia moorei (Odonata: Corduliidae) of Hazara Region, Pakistan - Sardar Azhar Mehmood; Shabir Ahmed; Ahmed Zia; Wali Khan; Waheed Ali Panhwar (Proceedings of the Zoological Society, 2024)

Diversity, species richness and distribution of grasshoppers (Orthoptera: Acrididae) in Khairpur Sindh Pakistan - Waheed Ali Panhwar; Shabir Ahmed; Sardar Azhar Mehmood; Abdul Manan Shaikh; Wali Khan; Muzafar Shah (International Journal of Tropical Insect Science, 2024)

Application of mesenchymal stem cells derived from the umbilical cord or Wharton’s jelly and their extracellular vesicles in the treatment of various diseases - Ayyub Ali Patel; Asma'a H. Mohamed; Jasur Rizaev; Ayaz Khurram Mallick; Maytham T. Qasim; Waleed Al Abdulmonem; Azfar Jamal; Haroonrashid M. Hattiwale; Mohammad Azhar Kamal; Fuzail Ahmad (Tissue and Cell, 2024)

Stripe rust resistance gene Yr15 in Turkish and Kazakhstan wheat germplasms and the potential of Turkish wild emmer for stripe rust breeding - Faheem Shehzad Baloch; Amjad Ali; Daniyar Tajibayev; Muhammad Azhar Nadeem; Fatih Ölmez; Hüsnü Aktaş; Ahmad Alsaleh; Gönül Cömertpay; Mustafa Imren; Zemran Mustafa; Abdelfattah A. Dababat; Seung Hwan Yang (Genetic Resources and Crop Evolution, 2024)

Exploring the variability of root system architecture under drought stress in heat-tolerant spring-wheat lines - Asadullah; Shahmir Ali Kalhoro; Wajid Farhad; Azhar Iqbal; Sultan; Abdul Waheed; Muhammad Rashid; Syed Rehmat Ullah Shah (Plant and Soil, 2024)
Background and aims Global wheat production is under threat due to climate change, specifically heat and drought and their combination. This study aims to address the root trait responses of heat-tolerant wheat genotypes to drought. Methods The variability in root traits of CIMMYT wheat lines, which were previously developed for heat stress tolerance (HTWL), was evaluated alongside 10 Pakistani-approved varieties under three cultivation conditions and soil moisture levels. Results Our findings revealed that the plasticity of the wheat root system is highly pronounced, with rhizosphere conditions exerting a more substantial influence (5–49%) than the genotypic response (1–14%). Furthermore, in the hydroponic and pot system, we noted higher maximum-root length (1.5–1.8 fold) and root-to-shoot ratio (3.4–10.6 fold) as compared to field condition, while the root biomass was substantially higher in the field trial (3-57 fold). Nonetheless, persistent drought conditions exerted contrasting impact with reduction in most of the traits except specific root length and harvest index which were increased under drought. Conclusions The variation in root traits against drought indicates the potential for the development of improved genotypes that can withstand multiple stresses. Furthermore, it is crucial to consider rhizosphere conditions when selecting genotypes, as the plasticity of wheat roots may lead to misinterpretations if rhizosphere conditions are disregarded. Root dry weight and root-to-shoot ratio are more stable traits as compared to maximum root length and specific root length. It is recommended to evaluate a broader range of rhizosphere conditions to select tolerant genotypes.

Characteristics and health implications of fine particulate matter near urban road site in Islamabad, Pakistan - Sabir Hussain; Azhar Siddique; Mujtaba Hassan; Kashif Rasool; Asif Shahzad; Syed Ali Asad Naqvi; Muhammad Raza Ul Mustafa (Environmental Research, 2024)

Assessing bioenergy prospects of algal biomass and yard waste using an integrated hydrothermal carbonization and pyrolysis (HTC–PY): A detailed emission–to–ash characterization via diverse hyphenated analytical techniques and modelling strategies - Akash Kumar; Imtiaz Ali Jamro; Hongwei Rong; Lata Kumari; Azhar Ali Laghari; Baihui Cui; Moses Akintayo Aborisade; Belay Tafa Oba; François Nkinahamira; Pamphile Ndagijimana; Shahdev Sajnani; Waheed Ali Bhagat; et al. (Chemical Engineering Journal, 2024)

Mechanistic approach of tannery wastewater and sulfadiazine mutual toxicity in wheat (Triticum aestivum L.) and mitigation through exogenous application of gallic acid. - Muhammad Nafees; Muhammad Azhar Ali; Linlin Qiu; Ying Yin; Meiling Xu; Guobing Wang; Shafaqat Ali; Hongyan Guo (Chemosphere, 2024)

Multi enzyme production from mixed untreated agricultural residues applied in enzymatic saccharification of lignocellulosic biomass for biofuel - Azhar Ali Tunio; Muhammad Naqvi; Abdul Sattar Qureshi; Imrana Khushk; Abdul Nabi Jatt; Abdul-Sattar Nizami; Habib Ahmed Naqvi; Tanzeel Rehman Charan; Miher Ali Bhutto; Nazir Ahmed Tunio; Qamer-u-Nisa (Process Safety and Environmental Protection, 2024)

Photocatalytic and biological efficacy of Carissa macrocarpa fruit extract-mediated one-pot synthesized ternary metal oxide dual S-scheme heterojunction - Abu Bakar Siddique; Muhammad Ashraf Shaheen; Azhar Abbas; Yasir Zaman; Akbar Ali; Muhammad Naeem-ul-Hassan; Javed Iqbal (Journal of Environmental Chemical Engineering, 2024)

Non-thermal pasteurization of milk by elongated electrode moderate electrical field: Chemical and sensory analysis during cold storage and shelf-life determination - Ali Wali M. Alsaedi; Asaad R. Al-Hilphy; Azhar J. Al-Mousawi; Mohsen Gavahian (Innovative Food Science & Emerging Technologies, 2024)

Characterisation of the protein quality and composition of water kefir-fermented casein - Mohammad Alrosan; Thuan-Chew Tan; Azhar Mat Easa; Sana Gammoh; Muhammad H. Alu'datt; Stan Kubow; Ali Madi Almajwal; Sofyan Maghaydah; Ammar A. Razzak Mahmood; Ali Al-Qaisi; Haya AlFandi (Food Chemistry, 2024)

Evaluation of drought hazards and coping strategies adopted by pastoral communities in the Cholistan Rangeland of Pakistan - Muhammad Farooq Azhar; Muhammad Junaid Faiz; Ehsan Ali; Abida Aziz; Muhammad Akbar; Ghulam Raza; Muhammad Abdullah; Muhammad Muzammil Habib; Muhammad Farooq Akram (Environmental Development, 2024)

Comparative study of light-emitting cement and polymer mortars for sustainable building applications: performance evaluation and analysis - Muhammad Ali Sikandar; Zeeshan Khan; Muhammad Haris Javed; Muhammad Tariq Bashir; Easa Khan; Md. Munir Hayet Khan; Azhar Qazi (Innovative Infrastructure Solutions, 2024)

Superoleophilic cotton fabric decorated with hydrophobic Zn/Zr MOF nanoflowers for efficient self-cleaning, UV-blocking, and oil–water separation - Naseer Ahmad; Sufian Rasheed; Tooba Ali; Irfan Azhar; Waqas Ahmad; Dilshad Hussain (Chemical Engineering Journal, 2024)

Artificial intelligence models for validating and predicting the impact of chemical priming of hydrogen peroxide (H2O2) and light emitting diodes on in vitro grown industrial hemp (Cannabis sativa L.) - Muhammad Aasim; Buşra Yıldırım; Ahmet Say; Seyid Amjad Ali; Selim Aytaç; Muhammad Azhar Nadeem (Plant Molecular Biology, 2024)

Synthesis of coal-biomass blended fuel through coal-wet briquetting technology - Ghulam Haider; Shaine Mohammadali Lalji; Syed Imran Ali; Faiq Azhar Abbasi; Muneeb Burney (Arabian Journal of Geosciences, 2024)

Effects of agro based organic amendments on growth and cadmium uptake in wheat and rice crops irrigated with raw city effluents: Three years field study - Hiba Shaghaleh; Muhammad Azhar; Muhammad Zia-ur-Rehman; Yousef Alhaj Hamoud; Ammar Ali Adam Hamad; Muhammad Usman; Muhammad Rizwan; Jean Wan Hong Yong; Hesham F. Alharby; Abdullah G. Al-Ghamdi; Basmah M. Alharbi (Environmental Pollution, 2024)

Glucanase Gene of Trichoderma; New Strategy for the Management of Root Rot Disease in Chili - Kiran Nawaz; Waheed Anwar; Muhamamd Nasir Subhani; Adnan Akhter; Sehrish Iftikhar; Hafiz Azhar Ali Khan; Ahmad Ali Shahid (Journal of Soil Science and Plant Nutrition, 2024)

Resistance risk assessment, cross-resistance potential and realized heritability of resistance to methomyl in Musca domestica Linnaeus - Hafiz Azhar Ali Khan (Ecotoxicology, 2024)

Micro/nanoplastics: Critical review of their impacts on plants, interactions with other contaminants (antibiotics, heavy metals, and polycyclic aromatic hydrocarbons), and management strategies - Ali Raza Khan; Zaid Ulhassan; Guanlin Li; Jiabao Lou; Babar Iqbal; Abdul Salam; Wardah Azhar; Sundas Batool; Tingting Zhao; Kexin Li; Qiuyue Zhang; Xin Zhao; et al. (Science of The Total Environment, 2024)

Evaluating the behaviour of axially loaded hollow concrete block masonry walls with small-size openings: Various opening positions and their influence on experimental results - Abrahem A. Ali Blash; B.H. Abu Bakar; Ufuoma Joseph Udi; Azhar Ayad Jaafar; Ilyani Akmar Abu Bakar; Nursyamsi Nursyamsi (Engineering Structures, 2024)

An experimental study on early age compression and shear strength properties of mixed clay soil - Azhar Abbas; Muhammad Akbar; Pan Huali; Ali Zar; Samar Ramzan; Zahoor Hussain (Arabian Journal of Geosciences, 2024)

Phytochemical screening and antimicrobial potential of Chenopodium quinoa extract against pathogenic bacterial strains - Hina Anwar; Arslan Habib; Muhammad Usman Taj; Muhammad Azhar Ali; Ayesha Munir; Marva Shafi; Maria Saddique; Sohaib Ahmed; Henrique D. M. Coutinho (Vegetos, 2024)

Synergistic effect of CuO and Sr doped g-C3N4 for CO2 photoreduction into hydrocarbon fuels - Adil Raza; Azhar Ali Haidry; Zhengjun Yao; Muhammad Farooq Saleem; Asma A. Alothman; Saikh Mohammad (Chemical Engineering Journal, 2024)

Genome-wide association studies revealed DArTseq loci associated with agronomic traits in Turkish faba bean germplasm - Tolga Karaköy; Faruk Toklu; Eylem Tuğay Karagöl; Damla Uncuer; Yeter Çilesiz; Amjad Ali; Muhammad Azhar Nadeem; Hakan Özkan (Genetic Resources and Crop Evolution, 2024)

Characterizing the HMA gene family in dragon fruit (Selenicereus undatus L.) and revealing their response to multifactorial stress combinations and melatonin-mediated tolerance - Qamar U Zaman; Latif Ullah Khan; Muhammad Azhar Hussain; Asif Ali; Liu Hui; Aamir Ali Khokhar; Darya Khan; Hua-Feng Wang (South African Journal of Botany, 2023)

Efficacy of entomopathogenic fungi against three major stored insect pests, Rhyzopertha dominica, Sitophilus zeamais and Trogoderma granarium - Hafiz Azhar Ali Khan; Tiyyabah Khan (Journal of Stored Products Research, 2023)

Feasibility assessment of self-deicing concrete pavements with recycled CFRP reinforcement: Environmental and mechanical performance - Abdullah Al Moman; Ali Azhar Butt; Somayeh Nassiri (Resources, Conservation and Recycling, 2023)

Fluorescence Spectroscopy for the Assessment of Microbial Load in UVC Treated Water - Sana Imtiaz; Shahzad Anwar; Laiq Zada; Hina Ali; M. Saeed Khurram; Azhar Saeed; Muhammad Saleem (Journal of Fluorescence, 2023)

Efficacy of zinc-based nanoparticles in alleviating the abiotic stress in plants: current knowledge and future perspectives - Ali Raza Khan; Wardah Azhar; Xingming Fan; Zaid Ulhassan; Abdul Salam; Muhammad Ashraf; Yihua Liu; Yinbo Gan (Environmental Science and Pollution Research, 2023)

Genotype responsive growth performance and salinity tolerance of tilapia hybrid (Oreochromis niloticus × O. mossambicus) - Bhakta Supratim Sarker; Md. Shamim Reza Sabuz; Md. Golam Azom; Nusrat Easmin; Azhar Ali; Md. Samsul Alam; M. Sadiqul Islam (Aquaculture, 2023)

Natural occurrence of fungal species on the rice weevil, Sitophilus oryzae (Coleoptera: Curculionidae), in Punjab, Pakistan - Tiyyabah Khan; Hafiz Azhar Ali Khan; Waheed Anwar; Muhammad Rizwan Khan; Muhammad Umer (International Journal of Tropical Insect Science, 2023)

How various stakeholder pressure influences mega-project sustainable performance through corporate social responsibility and green competitive advantage - Azhar Ali; Li Ma; Mohsin Shahzad; Jonathan Musonda; Shahid Hussain (Environmental Science and Pollution Research, 2023)

Literature review on pavements and electric vehicle interaction: A research roadmap - Thomas Mattinzioli; Ali Azhar Butt; John Harvey (Transportation Research Part D: Transport and Environment, 2023)

Effect of temperature and relative humidity on the efficacy of spinetoram against Sitophilus granarius, Sitophilus zeamais and Tribolium castaneum - Hafiz Azhar Ali Khan (Journal of Stored Products Research, 2023)

Seed priming with nano-silica effectively ameliorates chromium toxicity in Brassica napus - Zaid Ulhassan; Su Yang; Di He; Ali Raza Khan; Abdul Salam; Wardah Azhar; Sajid Muhammad; Skhawat Ali; Yasir Hamid; Imran Khan; Mohamed Salah Sheteiwy; Weijun Zhou (Journal of Hazardous Materials, 2023)

Recent advances in chromosome capture techniques unraveling 3D genome architecture in germ cells, health, and disease - Nuruliarizki Shinta Pandupuspitasari; Faheem Ahmed Khan; Chunjie Huang; Azhar Ali; Muhammad Rizwan Yousaf; Farwa Shakeel; Ezi Masdia Putri; Windu Negara; Anis Muktiani; Bambang Waluyo Hadi Eko Prasetiyono; Limbang Kustiawan; Dimar Sari Wahyuni (Functional & Integrative Genomics, 2023)

Non-thermal pasteurization of milk by an innovative energy-saving moderate electrical field equipped with elongated electrodes and process optimization - Ali Wali M. Alsaedi; Azhar J. Al-Mousawi; Asaad R. Al-Hilphy; Mohsen Gavahian (Innovative Food Science & Emerging Technologies, 2023)

Increased health risk assessment in different vegetables grown under untreated sewerage irrigation regime due to higher heavy metals accumulation - Zeshan Hassan; Ammara Hassan; Muhaiman Riaz; Azhar Abbas Khan; Sami Ul-Allah; Umbreen Shehzad; Muhammad Khurshid; Ali Bakhsh; Jawad Munawar Shah; Zahid Manzoor (Environmental Science and Pollution Research, 2023)

Cyclic loading effect on batter anchored pile group in dry sand - Ali H. Ahmed; Hassan O. Abbas; Azhar S. Ibrahim (Geotechnical and Geological Engineering, 2023)

Toxicity, resistance and metabolic mechanism of resistance to permethrin in larvae of laboratory and field strains of Musca domestica L. - Hafiz Azhar Ali Khan; Sumaira Maqsood; Anas Mahmood (Journal of Asia-Pacific Entomology, 2023)

A systematic literature review on public participation in decision-making for local authority planning: A decade of progress and challenges - Azlan Abas; Kadir Arifin; Mohd Azhar Mohamed Ali; Muhammad Khairil (Environmental Development, 2023)

Artificial neural network and decision tree facilitated prediction and validation of cytokinin-auxin induced in vitro organogenesis of sorghum (Sorghum bicolor L.) - Muhammad Aasim; Seyid Amjad Ali; Muhammad Tanveer Altaf; Amjad Ali; Muhammad Azhar Nadeem; Faheem Shahzad Baloch (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Conservation strategy, phytochemical diversity, and genetic consistency assessment of in vitro propagated perennial herb Vincetoxicum hirundinaria Medik - Ajmal Khan; Azhar Hussain Shah; Niaz Ali; Abdul Majid; Saad Hussain Shah (In Vitro Cellular & Developmental Biology - Plant, 2023)

Application of KHSO5 for remediation of soils polluted by organochlorides: A comprehensive study on the treatment's efficacy, environmental implications, and phytotoxicity - Belay Tafa Oba; Xuehao Zheng; Moses Akintayo Aborisade; Akash Kumar; Ashenafi Yohannes Battamo; Jiashu Liu; Azhar Ali Laghari; Peizhe Sun; Yongkui Yang; Lin Zhao (Science of The Total Environment, 2023)

Mode of inheritance of field-evolved resistance to pirimiphos-methyl in Sitophilus oryzae (Linnaeus) (Coleoptera: Curculionidae) - Hafiz Azhar Ali Khan; Tiyyabah Khan (Journal of Stored Products Research, 2023)

Spinach-derived boron-doped g-C3N4/TiO2 composites for efficient photo-degradation of methylene blue dye - Sadia Faryad; Umair Azhar; Muhammad Bilal Tahir; Wahid Ali; Muhammad Arif; Muhammad Sagir (Chemosphere, 2023)

Modelling wellbeing of farmers by using nexus of climate change risk perception, adaptation strategies, and their drivers on irrigation water in Pakistan - Muhammad Usman; Asghar Ali; Muhammad Khalid Bashir; Sajjad Ahmad Baig; Khalid Mushtaq; Azhar Abbas; Rimsha Akram; Muhammad Shahzad Iqbal (Environmental Science and Pollution Research, 2023)

MSR influence on environmental & ecological balance: Mediating effect of environmental regulations & strategies - Li Ma; Jonathan Musonda; Azhar Ali (Journal of Cleaner Production, 2023)

Pyrolysis of de-fatted microalgae residue: A study on thermal-kinetics, products’ optimization, and neural network modelling - Akash Kumar; Imtiaz Ali Jamro; Beibei Yan; Zhanjun Cheng; Junyu Tao; Shengquan Zhou; Lata Kumari; Jian Li; Moses Akintayo Aborisade; Belay Tafa Oba; Waheed Ali Bhagat; Azhar Ali Laghari; et al. (Fuel, 2023)

A Review and Perspective of Environmental Disinfection Technology Based on Microwave Irradiation - Liming Liu; Na Wang; Azhar Ali Laghari; Hong Li; Can Wang; Zhenyu Zhao; Xin Gao; Qiang Zeng (Current Pollution Reports, 2023)

Climate-induced optimal wheat cropping season and mapping districts vulnerabilities in Punjab, Pakistan - Azhar Ali Janjua; Muhammad Aslam (Environment, Development and Sustainability, 2023)

Melatonin-mediated resistance to copper oxide nanoparticles-induced toxicity by regulating the photosynthetic apparatus, cellular damages and antioxidant defense system in maize seedlings - Ali Raza Khan; Xingming Fan; Abdul Salam; Wardah Azhar; Zaid Ulhassan; Jiaxuan Qi; Fiza Liaquat; Shuaiqi Yang; Yinbo Gan (Environmental Pollution, 2023)

Evaluation of operational and financial viability models of combined landfill site for intermediate cities in Pakistan - Abdullah Yasar; Salman Basit; Amt-ul Bari Tabinda; Azhar Ali; Syeda Um-e-Kalsoom Naqvi; Abdul-Sattar Nizami; Syeda Laiba Haider Naqvi; Shakeel Mahmood; Rameesha Tanveer (Environmental Science and Pollution Research, 2023)

The influence of compost amendments on bioaccumulation of potentially toxic elements by pea plant cultivated in mine degraded soils - Abdulnour Ali Jazem Ghanim; Muhammad Azhar Shah; Mehboob Alam; Anwarzeb Khan; Muhammad Amjad Khan; Saifur Rahman; Mabkhoot A. Alsaiari; Mohammed Jalalah; Mohammad Kamal Asif Khan; Muhammad Irfan; Zawar Hussain (Arabian Journal of Geosciences, 2023)

A walk of corporate sustainability towards sustainable development: a bibliometric analysis of literature from 2005 to 2021 - Ahmad Ali Jan; Fong-Woon Lai; Junaid Siddique; Muhammad Zahid; Syed Emad Azhar Ali (Environmental Science and Pollution Research, 2022)

Taxonomy and distribution of butterfly fauna of family pieridae (lepidoptera) in district abbottabad, Khyber Pakhtunkhwa, Pakistan - Sidra Taj; Shoaib Ali; Shabir Ahmed; Muhammad Ather Rafi; Sardar Azhar Mehmood; Muzafar Shah (International Journal of Tropical Insect Science, 2022)

Selection for resistance to pirimiphos-methyl, permethrin and spinosad in a field strain of Sitophilus oryzae: resistance risk assessment, cross-resistance potential and synergism of insecticides - Tiyyabah Khan; Hafiz Azhar Ali Khan; Muhammad Saleem Haider; Waheed Anwar; Adnan Akhter (Environmental Science and Pollution Research, 2022)

Ethylene accelerates copper oxide nanoparticle-induced toxicity at physiological, biochemical, and ultrastructural levels in rice seedlings - Wardah Azhar; Ali Raza Khan; Abdul Salam; Zaid Ulhassan; Jiaxuan Qi; Gulmeena shah; Yihua Liu; Yang Chunyan; Shuaiqi Yang; Yinbo Gan (Environmental Science and Pollution Research, 2022)

Biopesticides and insect pest management - Kanwal Hanif; Muhammad Zubair; Dilbar Hussain; Sikander Ali; Muhammad Saleem; Hafiz Azhar Ali Khan; Tamsila Nazir; Muhammad Waqas ul Hassan (International Journal of Tropical Insect Science, 2022)

Pathogenic role of cytokines in COVID-19, its association with contributing co-morbidities and possible therapeutic regimens - Ayesha Tanveer; Bushra Akhtar; Ali Sharif; Uzma Saleem; Azhar Rasul; Aftab Ahmad; Kashif Jilani (Inflammopharmacology, 2022)

Light-emitting diodes induced in vitro regeneration of Alternanthera reineckii mini and validation via machine learning algorithms - Muhammad Aasim; Seyid Amjad Ali; Pınar Bekiş; Muhammad Azhar Nadeem (In Vitro Cellular & Developmental Biology - Plant, 2022)

Toxicity of selected organophosphate and pyrethroid insecticides against larval and adult stages of Culex quinquefasciatus - Muhammad Zubair; Hafiz Azhar Ali Khan; Waseem Akram; Khurram Zia; Rana Muhammad Naeem Ahsan; Malik Muhammad Shahbaz Sharif; Huma Qamar; Muhammad Kamil Malik (International Journal of Tropical Insect Science, 2022)

Potential of Fish Scale Biochar Nanocomposite with ZnO for Effective Sequestration of Cr (VI) from Water: Modeling and Kinetics - Azhar Ul Islam; Muhammad Mohsin Iqbal; Muhammad Imran; Muhammad Adnan Tariq; Muhammad Nadeem; Muhammad Qasim Kakar; Muhammad Nawaz; Muhammad Amjad; Saeed Ahmad Qaisrani; Muhammad Rizwan; Shafaqat Ali (International Journal of Environmental Research, 2022)

In Vivo Effects of Orally Administered Different Concentrations of Silver Oxide Nanoparticles in Hyperuricemic Mice - Mubin Mustafa Kiyani; Nurain Baig Moghul; Ambreen Javed; Maisra Azhar Butt; Hassan Burair Abbas; Hamza Rehman; Tausif Ahmed Rajput; Syed Ali Imran Bokhari (Biological Trace Element Research, 2022)

Assessment of genetic diversity among 131 safflower (Carthamus tinctorius L.) accessions using peroxidase gene polymorphism (POGP) markers - Mehtap Yildiz; Muhammad Tanveer Altaf; Faheem Shehzad Baloch; Metin Koçak; Gökhan Sadık; Cansu Kuzğun; Muhammad Azhar Nadeem; Fawad Ali; Mehmet Bedir; Murat Tunçtürk (Molecular Biology Reports, 2022)

Inoculation of Azospirillum brasilense and exogenous application of trans-zeatin riboside alleviates arsenic induced physiological damages in wheat (Triticum aestivum) - Muhammad Saqlain Zaheer; Hafiz Haider Ali; Kehinde O. Erinle; Shabir Hussain Wani; Okon Godwin Okon; Muhammad Azhar Nadeem; Muhammad Nawaz; Muhammad Adnan Bodlah; Muhammad Mohsin Waqas; Javaid Iqbal; Ali Raza (Environmental Science and Pollution Research, 2022)

The role of selected odonate nymphs in biological control of Culex quinquefasciatus larvae, and effect of glyphosate herbicide on their predatory performance - Sami Ullah Khan; Sardar Azhar Mehmood; Hazrat Ali; Waqas Waqas; Bakht Rahbar (International Journal of Tropical Insect Science, 2022)

Anti-Hyperuricemic Effect of Iron Oxide Nanoparticles against Monosodium Urate Crystals Induced Gouty Arthritis in BALB/c Mice - Mubin Mustafa Kiyani; Nurain Baig Moghul; Maisra Azhar Butt; Hamza Rehman; Ramsha Masood; Tausif Ahmed Rajput; Syed Ali Imran Bokhari (Biological Trace Element Research, 2022)

Evaluation of Antioxidant Activity and Histopathological Changes Occurred by the Oral Ingestion of CuO Nanoparticles in Monosodium Urate Crystal-Induced Hyperuricemic BALB/c Mice - Mubin Mustafa Kiyani; Maisra Azhar Butt; Hamza Rehman; Moheen Mustafa; Abdul Ghafoor Sajjad; Syed Sajid Hussain Shah; Tariq Mahmood; Syed Ali Imran Bokhari (Biological Trace Element Research, 2022)

Comparative analysis of chicken cecal microbial diversity and taxonomic composition in response to dietary variation using 16S rRNA amplicon sequencing - Zubia Rashid; Muhammad Zubair Yousaf; Syed Muddassar Hussain Gilani; Sitwat Zehra; Ashaq Ali; Abid Azhar; Saddia Galani (Molecular Biology Reports, 2021)

Antifouling paint biocides (Irgarol 1051 and diuron) in the selected ports of Peninsular Malaysia: occurrence, seasonal variation, and ecological risk assessment - Hassan Rashid Ali; Marinah Mohd Ariffin; Tuan Fauzan Tuan Omar; Adiana Ghazali; Mohammed Ali Sheikh; Noor Azhar Mohamed Shazili; Zainudin Bachok (Environmental Science and Pollution Research, 2021)

Do risk perceptions and constraints influence the adoption of climate change practices among small livestock herders in Punjab, Pakistan? - Muhammad Faisal; Xia Chunping; Azhar Abbas; Muhammad Haseeb Raza; Shoaib Akhtar; Muhammad Arslan Ajmal; Abdelrahman Ali (Environmental Science and Pollution Research, 2021)

Pyriproxyfen induces lethal and sublethal effects on biological traits and demographic growth parameters in Musca domestica - Hafiz Azhar Ali Khan (Ecotoxicology, 2021)

Lead contamination in shooting range soils and its phytoremediation in Pakistan: a greenhouse experiment - Amir Zeb Khan; Sardar Khan; Said Muhammad; Shams Ali Baig; Abdullah Khan; Muhammad Jamal Nasir; Madiha Azhar; Alia Naz (Arabian Journal of Geosciences, 2021)

Evaluating the relationship between climate variability and agricultural crops under indeterminacy - Azhar Ali Janjua; Muhammad Aslam; Naheed Sultana (Theoretical and Applied Climatology, 2020)

Integrated Application of Organic Amendments with Alcaligenes sp. AZ9 Improves Nutrient Uptake and Yield of Maize (Zea mays) - Azhar Hussain; Maqshoof Ahmad; Muhammad Zahid Mumtaz; Sajjad Ali; Rubab Sarfraz; Muhammad Naveed; Moazzam Jamil; Christos A. Damalas (Journal of Plant Growth Regulation, 2020)

Phenolic Profile and Thermal Stability of Monovarietal Extra Virgin Olive Oils Based on Synchronous Fluorescence Spectroscopy - Hina Ali; Muhammad Azhar Iqbal; Babar Manzoor Atta; Rahat Ullah; Muhammad Bilal Khan (Journal of Fluorescence, 2020)

Molecular characterization of genetic diversity and similarity centers of safflower accessions with ISSR markers - Fawad Ali; Muhammad Azhar Nadeem; Ephrem Habyarimana; Abdurrahim Yılmaz; Muhammad Amjad Nawaz; Iftikhar Hussain Khalil; Sezai Ercişli; Gyuhwa Chung; Hassan Javed Chaudhary; Faheem Shehzad Baloch (Brazilian Journal of Botany, 2020)

Lipids as biomarkers of brain disorders - Ghulam Hussain; Haseeb Anwar; Azhar Rasul; Ali Imran; Muhammad Qasim; Shamaila Zafar; Muhammad Imran; Syed Kashif Shahid Kamran; Nimra Aziz; Aroona Razzaq; Waseem Ahmad; Asghar Shabbir; et al. (Critical Reviews in Food Science and Nutrition, 2020)

Comparative study of the genetic basis of nitrogen use efficiency in wild and cultivated barley - Jawad Munawar Shah; Sidra tul Muntaha; Essa Ali; Azhar Abbas Khan; Syed Hassan Raza Zaidi; Ahmad Naeem Shahzad; Zeshan Hassan; Ahmad Nawaz; Muhammad Rashid; Syed Asad Hussain Bukhari (Physiology and Molecular Biology of Plants, 2019)

Influence of biochar amendment and foliar application of iron oxide nanoparticles on growth, photosynthesis, and cadmium accumulation in rice biomass - Muhammad Rizwan; Shamaila Noureen; Shafaqat Ali; Sarwat Anwar; Muhammad Zia ur Rehman; Muhammad Farooq Qayyum; Azhar Hussain (Journal of Soils and Sediments, 2019)

Association analysis and allelic distribution of deletion in CC chemokine receptor 5 gene (CCR5Δ32) among breast cancer patients of Pakistan - Faria Fatima; Saima Saleem; Abdul Hameed; Ghulam Haider; Syed Aqib Ali Zaidi; Madiha Kanwal; Sitwat Zehra; Abid Azhar (Molecular Biology Reports, 2019)

Genome-wide identification and expression analyses of WRKY transcription factor family members from chickpea (Cicer arietinum L.) reveal their role in abiotic stress-responses - Muhammad Waqas; Muhammad Tehseen Azhar; Iqrar Ahmad Rana; Farrukh Azeem; Muhammad Amjad Ali; Muhammad Amjad Nawaz; Gyuhwa Chung; Rana Muhammad Atif (Genes & Genomics, 2019)

Occurrence of Aflatoxin M1 in raw and processed milk and assessment of daily intake in Lahore, Multan cities of Pakistan - Mateen Ahmad; Muhammad Awais; Shinawar Waseem Ali; Hafiz Azhar Ali Khan; Muhammad Riaz; Asif Sultan; Muhammad Shakeel Bashir; Adnan Ishtiaq Chaudhry (Food Additives & Contaminants Part B-Surveillance, 2019)

Role of viruses, prions and miRNA in neurodegenerative disorders and dementia - Sayed Sartaj Sohrab; Mohd Suhail; Ashraf Ali; Mohammad Amjad Kamal; Azamal Husen; Fahim Ahmad; Esam Ibraheem Azhar; Nigel H. Greig (VirusDisease, 2018)

Influence of salinity and Fusarium oxysporum as the stress factors on morpho-physiological and yield attributes in onion - Amna Shoaib; Sidra Meraj; Nafisa; Kashif Ali Khan; Muhammad Azhar Javaid (Physiology and Molecular Biology of Plants, 2018)

A field study investigating the potential use of phosphorus combined with organic amendments on cadmium accumulation by wheat and subsequent rice - Muhammad Zia ur Rehman; Muhammad Rizwan; Shafaqat Ali; Asif Naeem; Balal Yousaf; Guijian Lui; Hinnan Khalid; Saifullah; Farhan Hafeez; Muhammad Azhar (Arabian Journal of Geosciences, 2018)

Consequence of HIV and HCV co-infection on host immune response, persistence and current treatment options - Sayed Sartaj Sohrab; Mohd Suhail; Ashraf Ali; Ishtiaq Qadri; Steve Harakeh; Esam I. Azhar (VirusDisease, 2018)

A machine learning framework involving EEG-based functional connectivity to diagnose major depressive disorder (MDD) - Wajid Mumtaz; Syed Saad Azhar Ali; Mohd Azhar Mohd Yasin; Aamir Saeed Malik (Medical & Biological Engineering & Computing, 2018)

How hard they hit? Perception, adaptation and public health implications of heat waves in urban and peri-urban Pakistan - Sara Rauf; Khuda Bakhsh; Azhar Abbas; Sarfraz Hassan; Asghar Ali; Harald Kächele (Environmental Science and Pollution Research, 2017)

Natural products from Cuscuta reflexa Roxb . with antiproliferation activities in HCT116 colorectal cell lines - Muhammad Riaz; Aishah Bilal; Muhammad Shaiq Ali; Itrat Fatima; Amir Faisal; Muhammad Azhar Sherkheli; Adnan Asghar (Natural Product Research, 2017)

Photosynthesis and growth response of maize (Zea mays L.) hybrids exposed to cadmium stress - Tasneem Akhtar; Muhammad Zia-ur-Rehman; Asif Naeem; Rab Nawaz; Shafaqat Ali; Ghulam Murtaza; Muhammad Aamer Maqsood; Muhammad Azhar; Hinnan Khalid; Muhammad Rizwan (Environmental Science and Pollution Research, 2017)

Genetics and mechanism of resistance to deltamethrin in the house fly, Musca domestica L., from Pakistan - Hafiz Azhar Ali Khan; Waseem Akram; Muhammad Saleem Haider (Ecotoxicology, 2015)

Comparison between regression and ANN models for relationship of soil properties and electrical resistivity - Fahad Irfan Siddiqui; Dur Muhammad Pathan; Syed Baharom Azhar Bin Syed Osman; Munawar Ali Pinjaro; Safiullah Memon (Arabian Journal of Geosciences, 2015)

Resistance of the house fly Musca domestica (Diptera: Muscidae) to lambda-cyhalothrin: mode of inheritance, realized heritability, and cross-resistance to other insecticides - Naeem Abbas; Hafiz Azhar Ali Khan; Sarfraz Ali Shad (Ecotoxicology, 2014)

A new trypsin inhibitory phthalic acid ester from Heliotropium strigosum - Syed Majid Shah; Azhar-ul-Haq Ali Shah; Farhat Ullah; Sajid Hussain; Sher Bahadar Khan; Abdullah M. Asiri; Shabir Ahmad; Hidayatullah Khan; Umar Farooq (Medicinal Chemistry Research, 2014)

Cattle egrets as a biosentinels of persistent organic pollutants exposure - Mudassar Khan; Ashiq Mohammad; Karam Ahad; Athanasios Katsoyiannis; Salman Akbar Malik; Muhammad Abdullaha; Azhar Rashid; Mauro Fasola; Alamdar Hussain; Habib Bokhari; Syed Ali Musstjab Akber Shah Eqani (Environmental Geochemistry and Health, 2014)

Resistance to conventional insecticides in Pakistani populations of Musca domestica L. (Diptera: Muscidae): a potential ectoparasite of dairy animals - Hafiz Azhar Ali Khan; Waseem Akram; Sarfraz Ali Shad (Ecotoxicology, 2013)

Dracorhodin perchlorate inhibits PI3K/Akt and NF-κB activation, up-regulates the expression of p53, and enhances apoptosis - Azhar Rasul; Chuan Ding; Xiaomeng Li; Muhammad Khan; Fei Yi; Muhammad Ali; Tonghui Ma (Apoptosis, 2012)

Antitussive and toxicological evaluation of Vitex negundo - Rizwan-ul Haq; Azhar-ul-Haq Ali Shah; Arif-ullah Khan; Zahoor Ullah; Habib-ullah Khan; Rafeeq Alam Khan; Abdul Malik (Natural Product Research, 2012)

Continuous Production of Dextran from Immobilized Cells of Leuconostoc mesenteroides KIBGE HA1 Using Acrylamide as a Support - Shah Ali Ul Qader; Afsheen Aman; Abid Azhar (Indian Journal of Microbiology, 2011)

Purification and Characterization of Novel α-Amylase from Bacillus subtilis KIBGE HAS - Saeeda Bano; Shah Ali Ul Qader; Afsheen Aman; Muhammad Noman Syed; Abid Azhar (AAPS PharmSciTech, 2011)